Supercontinuum generation with picosecond ultraviolet pulses in a solid-core photonic crystal fiber - Sylvestre, T.; Lee, M. W.; Ragueh, A. R.; Stiller, Birgit; Fanjoux, G.; Barviau, B.; Mussot, A.; Kudlinski, A. (Optics InfoBase Conference Papers, 2012)
Black light supercontinuum generation is demonstrated as a result of picosecond pumping a solid-core photonic crystal fiber at 355 nm through the combined effects of intermodal four-wave mixing and cascaded Raman scattering. © 2012 OSA.
CRIS-Team Scopus Importer:2021-06-29